Gerakan Masyarakat Hidup Sehat Sebagai Upaya Percepatan Penurunan Prevalensi Stunting Berbasis Keluarga - Hutagaol, Rutmauli; Mahdalena, Mahdalena; Mahpolah, Mahpolah; Irfa'i, Muhammad; Junaidi, Junaidi; Suroto, Suroto; Hamzani, Sulaiman; Elyn, Tini; Yuniarti, Yuniarti; Ulfah, Rasuna; Wulandari, Meggy; Pratiwi, Niken; Amalya, Vitha; Fahrunisa, Aina (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
Stunting is still a nutritional problem in children in Indonesia and several other developing countries. This has become a public health problem that must be taken seriously and requires continuity as this can cause irreversible damage both physically and cognitively to the child. Based on this, the government is making efforts to reduce Non-Communicable Diseases (NCDs) by promoting the Healthy Living Community Movement (HLCV) as a promotive and preventive effort. This community service activity was carried out by the Health Polytechnic of the health ministry Banjarmasin in collaboration with the Banjar District Health Office. This activity aims to improve the environment and change behavior towards a healthier one. As many as 250 participants were involved in this activity from various walks of life. The method used is socialization in the form of talk shows and discussions. In the discussion activity, the community enthusiastically asked questions related to the material provided. This indicates a change in attitude and behavior after socialization. It requires the commitment of all parties involved in efforts to tackle stunting, including making Germas one of the work programs that are carried out routinely.